2021
DOI: 10.17051/ilkonline.2021.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Game preferences of K-12 level students: analysis and prediction using the association rule

Abstract: Many different tools have accompanied the self-realization processes of human beings such as love, belonging, respect, socialization and gaining new experiences. These tools have differentiated depending on the development in science and technology or have been replaced by new tools. Games, on the other hand, have been constantly renewed by this process and have survived until today and have become an important industry today. In addition, games have become a frequent part of learning environment designs recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(77 reference statements)
0
1
0
1
Order By: Relevance
“…Considering the statistical analysis methods used in the study, it is important to evaluate the findings revealed by data mining. The association rule used in this study, although it is less used in educational sciences, has wide usage in several areas as Computer Science (Chen et al 2021), Engineering (Çakır et al, 2021), Decision Sciences (Prathama et al2021), Mathematics (Li et al, 2020) Business, Management and Accounting (Moodley et al, 2020), Medicine and Dentistry (Tandan et al, 2021), Social Sciences (Cömert & Akgün, 2021), Energy (Odabaşı & Yıldırım, 2019), Environmental Science (Nagata et al, 2014) and Psychology (Elia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the statistical analysis methods used in the study, it is important to evaluate the findings revealed by data mining. The association rule used in this study, although it is less used in educational sciences, has wide usage in several areas as Computer Science (Chen et al 2021), Engineering (Çakır et al, 2021), Decision Sciences (Prathama et al2021), Mathematics (Li et al, 2020) Business, Management and Accounting (Moodley et al, 2020), Medicine and Dentistry (Tandan et al, 2021), Social Sciences (Cömert & Akgün, 2021), Energy (Odabaşı & Yıldırım, 2019), Environmental Science (Nagata et al, 2014) and Psychology (Elia et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Teknologi berkembang dari hari ke hari, inovasi dengan cepat menjadi alami dari bagian kehidupan oleh karena itu anak perlu kreatif dengan menghasilkan inovasi terbaru, bermain mengembangkan keterampilan anak dalam memecahkan masalah (Sahni, 2023), pemikiran strategi, manajemen waktu, hal yang menyenangkan (Rubén Camacho-Sánchez et al, 2023). ekspresi verbal dan cepat dalam mengambil keputusan , serta anak mampu berpikir kritis (Bunt and Gouws, 2020), da melakukan analisis kritis (Cömert and Akgün, 2021).…”
Section: Mempertimbangkan Keamananunclassified